Grief Education in Accredited Counseling Programs: Tools for Integrating Grief Counseling Concepts into the CACREP Foundational Counseling Curriculum - Nicole A Stargell; Emily T. Smith; Gary W Mauk (Teaching and Supervision in Counseling, 2025)
Counselors working in a wide variety of settings should be competent in providing grief counseling. The current CACREP (2024) standards include grief education under lifespan development, but grief education can be woven throughout all eight domains of the foundational counseling curriculum. This article explains the foundational grief counseling concepts of attachment theory, the dual process model of grief, meaning-making theory, and adaptive grieving styles. Included in this article are suggestions for infusing these foundational grief counseling concepts into each of the eight CACREP foundational counseling curriculum areas.
Keywords: Grief; loss; CACREP; counselor education